Electropreconcentration‐induced local pH change. Issue 3 (24th November 2017) - Chun, Honggu
Abstract: Ion‐permselective nanochannel‐based sample preconcentration or electropreconcentration has been demonstrated as an effective technique for concentrating charged analytes at the interface between a micro‐ and nanochannel. The anion‐selective electropreconcentration involves extraction of hydroxide in the preconcentrated sample plug, resulting in pH decrease. We investigated the pH change in a microchannel using charged pH indicators with different conditions including running buffer pH, sample channel electric field, and salt concentration. The anion‐selective preconcentration showed pH decrease from 11 to under 7 in the preconcentrated sample plug. Therefore, careful design and interpretation are required with pH‐dependent experiments such as analyzing enzyme or antibody characteristics. The pH change could be mitigated by reducing the sample channel electric field and/or increasing salt concentration in the buffer.